Pengaruh Pemeriksaan Dan Pengawasan Keuangan Daerah Terhadap Kinerja Penyelenggaraan Pemerintah Daerah (Studi Empiris Pada Pemerintah Daerah Kabupaten / Kota Di Sumatera) - Adi Nugraha, Baskara, Drs. Suyatmin Waskito Adi, M.Si (2015)
This study, entitled "Effect of Inspection and Supervision of the Implementation of the Regional Financial Performance Against Local Government. This study aimed to examine the effect of the financial investigation of the State Audit Board of Indonesia BPK RI (internal control weaknesses the audit findings, the audit findings of noncompliance in the legislative and public oversight of local government performance regencies / cities in Sumatra. This study uses secondary data and the sampling technique used in this study using purposive sampling. This study uses multiple regression test. Results of the study: (1) weakness of the Internal Control System significant negative effect on the performance of local government administration. T_hitung value smaller than t_tabel (0.602 <2.032) with a significant value of more than 0.05 (0.551> 0.05), so the first hypothesis is not accepted. (2) Nonobservance legislation significant negative effect on the performance of local government administration. Value t_hitung> t_tabel (2,318> 2,032) with significantly smaller than 0.05 (0, 027 <0.05) ,, so that the second hypothesis is accepted. (3) Monitoring the public significant positive effect on the performance of local government administration. T_hitung value <t_tabel (-1057 <2.032) with a significant value of more than 0.05 (0.299> 0.05), so the third hypothesis tidakditerima.